2022
DOI: 10.1590/2175-8239-jbn-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mindfulness-based interventions in people undergoing hemodialysis: a systematic review

Abstract: Introduction: Chronic kidney disease (CKD) is a serious public health problem worldwide, leading to a series of physical and psychological comorbidities, in addition to costly treatments, lifestyle and dietary restrictions. There is evidence that mindfulness-based interventions (MBIs) offer complementary treatment for people with chronic illnesses, including CKD, with the aim of improving overall health, reducing side effects and treatment costs. This review aims to investigate the MBIs impact on people with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…However, this study found that MBIs have no significant effect on PD patients' self‐efficacy, which resonates with findings from another study conducted among HD patients who underwent mindfulness meditation (Solati et al, 2019). The recent literature also reported mixed results on how mindfulness can truly influence self‐efficacy (Fallah, 2017; Firth et al, 2019; Razzera et al, 2021). It is unclear how mindfulness directly affects self‐efficacy or, alternatively, its role as a mediator of self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study found that MBIs have no significant effect on PD patients' self‐efficacy, which resonates with findings from another study conducted among HD patients who underwent mindfulness meditation (Solati et al, 2019). The recent literature also reported mixed results on how mindfulness can truly influence self‐efficacy (Fallah, 2017; Firth et al, 2019; Razzera et al, 2021). It is unclear how mindfulness directly affects self‐efficacy or, alternatively, its role as a mediator of self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study conducted by Razzera et al (2022), to investigate the effect of mindfulness-based programs on chronic renal failure patients receiving hemodialysis treatment; mindfulness-based programs can offer a promising and safe complementary therapy for people with CRF undergoing hemodialysis, acting on quality of life and physical aspects of the disease. According to the study conducted by Nassim et al (2021), in patients undergoing dialysis, mindfulness-based programs may be helpful intervention for depression symptom.…”
Section: Discussionmentioning
confidence: 99%
“…However, most evidence for mindfulness interventions require several months of commitment from participants and are delivered in person, a significant barrier to engagement for people with chronic illness since the COVID-19 pandemic. There is a lack of research on the effectiveness of brief mindfulness interventions that are delivered remotely for people with kidney disease [ 17 ].…”
Section: Introductionmentioning
confidence: 99%